If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-5=1/5x+7
We move all terms to the left:
2x-5-(1/5x+7)=0
Domain of the equation: 5x+7)!=0We get rid of parentheses
x∈R
2x-1/5x-7-5=0
We multiply all the terms by the denominator
2x*5x-7*5x-5*5x-1=0
Wy multiply elements
10x^2-35x-25x-1=0
We add all the numbers together, and all the variables
10x^2-60x-1=0
a = 10; b = -60; c = -1;
Δ = b2-4ac
Δ = -602-4·10·(-1)
Δ = 3640
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{3640}=\sqrt{4*910}=\sqrt{4}*\sqrt{910}=2\sqrt{910}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-60)-2\sqrt{910}}{2*10}=\frac{60-2\sqrt{910}}{20} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-60)+2\sqrt{910}}{2*10}=\frac{60+2\sqrt{910}}{20} $
| 7y-6=20 | | 19p=-16 | | -28-4m=-2m-8(m-1) | | 11-16x=10x-3 | | –3.5(2–3n)–2.5=n | | -8y+3(y-3)=21 | | 5x^2+3=3x | | 7n-5=9n+12 | | 5+7(6-6x)=299 | | 8-8a=-3a-2 | | -16+5x-7+8=1+3x | | 7y/3=49 | | -2(7m+2)=-6(6m-3) | | -10=x+4x | | 6(6x+6)=-180 | | 35=-8(1-6a)+5(6a-7) | | w-8.55=4.3 | | 5x+3=3+7 | | u+6.31=9.18 | | 5x+3=3+17 | | v+4.5=9.46 | | 2x+6-5x+3=-8 | | 11/15=w+8/15 | | -8=g+-16 | | 226=-y+25 | | w-9.65=7.1 | | 176-v=129 | | 8-3x÷5=x | | u+2.55=8.61 | | 1+1x=2x-8 | | 12=k+17 | | 12-w=266 |